physical fitness model in increasing physical activity of female students of SDN 2 Perampuan - Abdul Wahab; Edi Kurniawan; Kokom Supriyatnak (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to demonstrate that a physical fitness-based learning model significantly contributes to increasing students' physical activity. Learning approaches that emphasize structured physical activity, movement variations, and active student engagement have been shown to improve students' fitness levels and participation in physical activity (Smith & McKenzie, 2018). Furthermore, a study by Lubans et al. (2016) confirmed that systematically designed physical education interventions can significantly increase students' active time (moderate-to-vigorous physical activity) in elementary school settings. This finding is further supported by research by Dale et al. (2019), which states that a physical activity-based learning model integrated into the curriculum can improve students' daily movement habits. In the context of education in Southeast Asia, research by Sulaiman and Hamzah (2020) shows that physical fitness learning packaged in the form of games and varied activities can increase students' motivation and engagement in physical activity. Similar findings were also found by Putra et al. (2021), who stated that an active learning approach in physical education has a positive impact on improving students' fitness and interest in sports. However, most previous studies have focused on improving general fitness, without specifically addressing changes in elementary school students' daily physical activity within the context of structured, fitness-based learning in elementary schools in specific areas. This situation indicates a research gap that needs to be filled. The scientific uniqueness of this study lies in the application of a physical fitness learning model contextualized to the conditions of elementary school students at SD 2 Perampuan. This study not only measures fitness improvements but also specifically analyzes changes in students' physical activity based on various indicators of daily and weekly activity, as well as the types of physical activity undertaken. Thus, this study provides a more comprehensive picture of the impact of learning models on students' physical activity behavior. This model also helps to shape healthy lifestyle habits and increase students' physical activity. During elementary school age, children are in a phase of very rapid motor development, making physical activity a crucial component in supporting their physical, cognitive, and social growth. However, in practice, students' physical activity levels are often suboptimal due to limited learning variations, low motivation to move, and the dominance of sedentary activities outside of school.